Effect of students’ investigative experiments on students’ recognition of interference and diffraction patterns: An eye-tracking study - Ana Susac (American Physical Society, 2021)
Recognition of interference and diffraction patterns is a difficult task for both high-school and university students. Many students fail to observe important features of particular patterns and identify the differences among similar patterns. In this study, we investigated if performing students’ investigative experiments can help high-school students in recognition of typical interference and diffraction patterns. Students in the experimental group were exposed to a teaching intervention that included five students’ investigative hands-on experiments on wave optics whereas the control group had the standard lecture-based physics teaching. We measured eye movements of students from both the experimental and control groups while they were identifying patterns produced by monochromatic light on a double slit, single slit, and diffraction grating, and by white light on a diffraction grating. Students from the experimental group had a higher percentage of correct answers than students in the control group that indicated that students’ investigative experiments had a positive effect on their recognition of interference and diffraction patterns. However, the low percentage of correct answers, even in the experimental group, confirms that distinguishing of the typical interference and diffraction patterns remains a difficult task for high-school students even if they had performed investigative hands-on experiments. Eye-tracking data showed that students from the experimental group had a shorter dwell on multiple-choice patterns, possibly because they were more familiar with interference and diffraction patterns and felt more confident in choosing the correct pattern. All students attended more to those patterns which they chose as the correct answer and that corroborates the previous findings. Overall, the results indicate that students’ recognition of interference and diffraction patterns can be improved by introducing hands-on investigative experiments in the classroom.